Pakistan : Request for a Three-Year Arrangement Under the Poverty Reduction Growth Facility. (IMF Staff Country Reports; Country Report, 2001)
Pakistan has established sound macroeconomic management and structural reforms under the Stand-By Arrangement. Executive Directors welcomed this step, and emphasized the need to maintain fiscal and monetary stances. They welcomed the Poverty Reduction and Growth Facility (PRGF) program, which focuses on the reform of tax policy and tax administration; public enterprise restructuring and privatization; raising growth and reducing poverty; and financial sector reforms. Directors urged the authorities for the full implementation of the reforms, and approved a Three-Year Arrangement for Pakistan under the PRGF Arrangement.